Place Of Information And Communication Technologies In Interaction In The Information Society - Мерщій, Т. В. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2019)
Introduction. Each historical time and cultural environment has its own peculiarities of social interaction. In the modern world, thanks to information and communication technologies, the process of interaction and its development is significantly changing. The culture of the information society is becoming the background on which a complex and heterogeneous system of interaction unfolds. Computer and information technology are transforming the existing forms of social interaction, contributing into the destruction of habitual communication. The aim of this article is to identify the place of information and communication technologies in the process of interaction in the information society. The tasks for achieving this goal are the comparison of the concepts of the philosophers F. Batsevich, Yu. Habermas, M. Bakhtin, according to which the basis of universal civilization development is a consistent change of types of communications, in particular the specificity of the functioning of the information space. Research methods. Socio-cultural and synergistic approaches will be used to achieve the goal and more specific research objectives. Research results. The historical development of society demonstrates various types of communication. Let us turn to the concepts closest to our study, according to which the basis of general civilizational development is a consistent change in types of communications: the concept of F. Batsevich's feedback, the idea of the uniqueness of the individual, the constant choice of his own identity of Yu. Habermas, the presence of a hypothetical contextualist audience of M. Bakhtin. Conclusion. The analysis makes it clear that the confrontation between traditions and innovations is increasing, the gaps between generations are widening, the hierarchy of values and priorities in the mass consciousness is changing, norms and patterns of behavior, practices and technologies of communication are being transformed. Information and communication technologies are the newest attribute of interaction in the conditions of informatization of society and an important factor of functioning of all its subsystems.